High On/Off Ratio Memristive Switching of Manganite/Cuprate Bilayer by Interfacial Magnetoelectricity. Issue 16 (27th May 2016) - Shen, Xiao; Pennycook, Timothy J.; Hernandez‐Martin, David; Pérez, Ana; Puzyrev, Yevgeniy S.; Liu, Yaohua; te Velthuis, Suzanne G. E.; Freeland, John W.; Shafer, Padraic; Zhu, Chenhui; Varela, Maria; Leon, Carlos; et al.
Abstract : Memristive switching serves as the basis for a new generation of electronic devices. Conventional memristors are two‐terminal devices in which the current is turned on and off by redistributing point defects, e.g., vacancies. Memristors based on alternative mechanisms have been explored, but achieving both high on/off ratio and low switching energy, as needed in applications, remains a challenge. This study reports memristive switching in La0.7 Ca0.3 MnO3 /PrBa2 Cu3 O7 bilayers with an on/off ratio greater than 10 3 and results of density functional theory calculations in terms of which it is concluded that the phenomenon is likely the result of a new type of interfacial magnetoelectricity. More specifically, this study shows that an external electric field induces subtle displacements of the interfacial Mn ions, which switches on/off an interfacial magnetic "dead layer", resulting in memristive behavior for spin‐polarized electron transport across the bilayer. The interfacial nature of the switching entails low energy cost, about of a tenth of atto Joule for writing/erasing a "bit". The results indicate new opportunities for manganite/cuprate systems and other transition metal oxide junctions in memristive applications. Abstract : When an external electric field is applied to a bilayer junction of La0.7 Ca0.3 MnO3 (LCMO) and PrBa2 Cu3 O7 (PBCO), it alters the positions of the Mn atoms at the LCMO/PBCO interface, turning On/Off a magnetic dead layer (MDL). The switching of MDL causes memristive hysteresis in the LCMO/PBCO bilayer junction.